Endoscopic extraction of living fasciola hepatica: Case report and literature review - Birol ÖZER; Ender SERİN; Yüksel GÜMÜRDÜLÜ; Gürden GÜR; Uğur YILMAZ; Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-